The Role of Bacterial Toxins and Environmental Factors in the Development of Food Allergies - Ahsanullah Unar; Muqaddas Qureshi; Hassan Imran Afridi; Shafkatullah Wassan (Allergies)
Food allergies (FAs) represent a significant and growing global health issue, with increasing prevalence across different age groups. This review provides a comprehensive analysis of the epidemiology, mechanisms, and risk factors involved in FA development. Currently, FAs are estimated to affect 2% of the general population, with higher rates in children (~8%). However, these figures may be inaccurate because of the reliance on self-reported data and immunoglobulin E (IgE) testing, which may not reflect clinically confirmed cases. Environmental and genetic factors, including exposure to bacterial toxins, dietary habits, and the gut microbiota, play critical roles in FA development. Specifically, Staphylococcus aureus enterotoxins are implicated in disrupting intestinal barriers and enhancing immune sensitization to allergenic proteins. This immune dysregulation promotes Th2 responses and compromises regulatory T cell function, crucial elements in allergy pathogenesis. As the prevalence of FAs continues to rise, there is a pressing need for accurate diagnostic tools, heightened public awareness, and effective prevention strategies. Further research is needed to elucidate the specific role of bacterial toxins and other environmental factors in FA development to advance clinical management approaches.